The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.14202/vetworld.2014.668-670
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of blood profiles between healthy and Brucella affected cattle

Abstract: Aim:The present investigation was undertaken to evaluate the blood biochemical metabolites of crossbred cattle suffering from brucellosis, in Khetri region of Kamrup District of Assam, India.Materials and Methods: Blood was collected by venipuncture from the jugular vein using 18 gauge hypodermic needle fitted to a Vacutainer-Leur adapter and evacuated tubes. Samples were screened for Brucella by rose Bengal plate test using plate test antigen. The study consisted of two groups. Group I consisted of healthy cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 8 publications
(10 reference statements)
3
10
3
1
Order By: Relevance
“…Furthermore, cows serologically positive for brucellosis had lower A/G ratios when compared with healthy cows. The result of the present study is partly in agreement with previous reports that documented an increase of serum globulin level in Brucella-affected cows (18), ewes (31), and camels (19), whereas Nath et al (18) reported a significant decrease in albumin concentrations and nonsignificant changes in total protein and A/G ratio between the brucellosis-affected and healthy cows. However, Hamada et al (31) found a nonsignificant difference in albumin and total protein between brucellosis-affected and healthy ewes.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, cows serologically positive for brucellosis had lower A/G ratios when compared with healthy cows. The result of the present study is partly in agreement with previous reports that documented an increase of serum globulin level in Brucella-affected cows (18), ewes (31), and camels (19), whereas Nath et al (18) reported a significant decrease in albumin concentrations and nonsignificant changes in total protein and A/G ratio between the brucellosis-affected and healthy cows. However, Hamada et al (31) found a nonsignificant difference in albumin and total protein between brucellosis-affected and healthy ewes.…”
Section: Discussionsupporting
confidence: 93%
“…The significantly increases of the liver enzyme (AST) in Brucella infected cows in comparison with the values of healthy cows indicates damage of the liver, which supports the earlier reports. 25,33,59 However, this study recorded lower level of ALT which contradicts the earlier reports. The insignificantly higher level of CK in Brucella-infected cows (1.82 ± 0.19) in comparison with healthy cows (0.96 ± 0.20) is in conformity with earlier reports.…”
Section: Discussioncontrasting
confidence: 99%
“…The current study revealed that the Brucellosis may be behind a significant elevation in serum total protein among tested buffalos which was similar to results recorded by Abou Eiazab in 2015 who found significant elevation in the total protein levels among cows infected with Brucella. Moreover other investigators reported significant increase in serum total protein among cattle infected with Brucellosis (Nath et al, 2014).…”
Section: Discussionmentioning
confidence: 87%
“…From the current study elevation in cholesterol, triglyceride and creatinine among tested cows were reported which was parallel to observations found by EL Bahgy and Ali in 2017. Moreover in a past study done by Nath et al, (2014), it was observed that serum cholesterol and triglyceride were significantly increased among cattle infected with Brucella. Also others recently found that total cholesterol and LDL values were increased while triglyceride, HDL and VLDL values were decreased among cattle with Brucellosis (Merhan et al, 2017).…”
Section: Discussionmentioning
confidence: 91%